Abnormal metabolism of gut microbiota reveals the possible molecular mechanism of nephropathy induced by hyperuricemia - Libin Pan; Pei Han; Shurong Ma; Ran Peng; Can Wang; Weijia Kong; Lin Cong; Jie Fu; Zhengwei Zhang; Hang Yu; Yan Wang; Jiandong Jiang (Elsevier, 2020)
The progression of hyperuricemia disease is often accompanied by damage to renal function. However, there are few studies on hyperuricemia nephropathy, especially its association with intestinal flora. This study combines metabolomics and gut microbiota diversity analysis to explore metabolic changes using a rat model as well as the changes in intestinal flora composition. The results showed that amino acid metabolism was disturbed with serine, glutamate and glutamine being downregulated whilst glycine, hydroxyproline and alanine being upregulated. The combined glycine, serine and glutamate could predict hyperuricemia nephropathy with an area under the curve of 1.00. Imbalanced intestinal flora was also observed. Flavobacterium, Myroides, Corynebacterium, Alcaligenaceae, Oligella and other conditional pathogens increased significantly in the model group, while Blautia and Roseburia, the short-chain fatty acid producing bacteria, declined greatly. At phylum, family and genus levels, disordered nitrogen circulation in gut microbiota was detected. In the model group, the uric acid decomposition pathway was enhanced with reinforced urea liver-intestine circulation. The results implied that the intestinal flora play a vital role in the pathogenesis of hyperuricemia nephropathy. Hence, modulation of gut microbiota or targeting at metabolic enzymes, i.e., urease, could assist the treatment and prevention of this disease. KEY WORDS: Hyperuricemia, Renal function, Gut microbiota, Metabolomics, Urease